2002
DOI: 10.1002/path.1129
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mRNA expression of tissue inhibitor of metalloproteinase‐1 (TIMP‐1) in breast carcinomas is correlated with adverse prognosis

Abstract: Tissue inhibitor of metalloproteinase-1 (TIMP-1) has emerged as a multifunctional protein with the contrasting activities of inhibiting tissue-degrading enzymes and promoting cellular growth. In an attempt to elucidate the clinical significance of TIMP-1 in breast cancer, the expression of TIMP-1 mRNA was evaluated in 117 invasive breast carcinomas by mRNA in situ hybridization, in correlation with clinicopathological parameters, immunohistochemical prognostic factors (Ki-67, c-erb-B-2, bcl-2) and clinical out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
61
3
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 30 publications
5
61
3
3
Order By: Relevance
“…In the evaluation of TIMP-1 as a prognostic marker in breast cancer, various methodologies have been used. Early studies measured TIMP-1 protein levels in tumor tissue by enzyme linked immunosorbent assay (ELISA) [10], or evaluated mRNA content [9] whereas later studies focused on TIMP-1 protein levels in blood [18,19] or evaluation by IHC [8,11,16]. Most studies fi nd high TIMP-1 protein levels to be associated with poor prognosis whereas only one study reports high TIMP-1 protein levels to be associated with good prognosis [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the evaluation of TIMP-1 as a prognostic marker in breast cancer, various methodologies have been used. Early studies measured TIMP-1 protein levels in tumor tissue by enzyme linked immunosorbent assay (ELISA) [10], or evaluated mRNA content [9] whereas later studies focused on TIMP-1 protein levels in blood [18,19] or evaluation by IHC [8,11,16]. Most studies fi nd high TIMP-1 protein levels to be associated with poor prognosis whereas only one study reports high TIMP-1 protein levels to be associated with good prognosis [11].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been suggested that the coexpression of various MMPs and/or tissular inhibitors of metalloproteinases (TIMPs) might provide additional prognostic information in breast cancer. Accordingly, it has been reported that several other MMPs and TIMPs may be overexpressed and/or related to clinical outcome in breast cancer, such as MMP-11 MT1-MMP (MMP-14) (Jones et al, 1999;Mimori et al, 2001) MMP-13 (Nielsen et al, 2001), TIMP-1 (Ree et al, 1997;McCarthy et al, 1999;Nakopoulou et al, 2002a;Schrohl et al, 2003Schrohl et al, , 2004 or TIMP-2 (Visscher et al, 1994;Ree et al, 1997;Remacle et al, 2000). In addition, there are at least two elements adding more complexity to the role of MMPs and TIMPs in cancer.…”
mentioning
confidence: 99%
“…It is a member of the TIMP family currently comprising four members (TIMP-1, -2, -3, and -4), is expressed by a wide range of cells, and is present in most tissues and body fluids (11,12). High levels of TIMP-1 mRNA as well as TIMP-1 protein have been found in several types of cancers including breast cancer, and this has been associated with a poor prognosis (13)(14)(15)(16)(17). That high levels of TIMP-1 predict a poor prognosis has been explained by at least two different models (4).…”
mentioning
confidence: 99%
“…TIMP-1 in complex with pro-MMP-9 (26) and with various activated MMPs and as uncomplexed TIMP-1. So far the prognostic value of only the total amount of TIMP-1 (uncomplexed TIMP-1 plus TIMP-1/MMP complexes) has been evaluated (13)(14)(15)(16)(17). In the case of other markers such as prostate-specific antigen it has been shown that specific fractions of the antigen carry useful clinical information (27), and we raised the hypothesis that this could also be the case for TIMP-1.…”
mentioning
confidence: 99%